2014
DOI: 10.1021/ja502885c
|View full text |Cite
|
Sign up to set email alerts
|

A Method for the Selective Hydrogenation of Alkenyl Halides to Alkyl Halides

Abstract: A general method for the selective hydrogenation of alkenyl halides to alkyl halides is described. Fluoro, chloro, bromo, iodo, and gem-dihaloalkenes are viable substrates for the transformation. The selectivity of the hydrogenation is consistent with reduction by a hydrogen atom transfer pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(102 citation statements)
references
References 78 publications
(29 reference statements)
1
93
1
4
Order By: Relevance
“…In 2014, we reported the reduction of alkenyl halides (e.g., 1 , Scheme 2) utilizing Co(acac) 2 , TBHP, and two reductants, triethylsilane and 1,4-dihydrobenzene (DHB) [2]. Mechanistic studies showed that Et 3 SiH participates in the formation of a cobalt hydride intermediate that delivers a hydrogen atom to the less-substituted position of the alkene.…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, we reported the reduction of alkenyl halides (e.g., 1 , Scheme 2) utilizing Co(acac) 2 , TBHP, and two reductants, triethylsilane and 1,4-dihydrobenzene (DHB) [2]. Mechanistic studies showed that Et 3 SiH participates in the formation of a cobalt hydride intermediate that delivers a hydrogen atom to the less-substituted position of the alkene.…”
Section: Resultsmentioning
confidence: 99%
“…473 Interestingly, the use of conjugated substrates including trans-4-phenyl-3-buten-2-one and cinnamaldehyde revealed that both CC and CO were completely reduced, affording the corresponding alcohols in 98% and 95% yields, respectively. Furthermore, mechanistic studies indicated that cobalt−ligand cooperativity was not 473 Herzon's group 474 reported a new route for the selective hydrogenation of alkenyl halides to alkyl halides catalyzed by [Co(acac) 2 ] through a HT pathway using both triethylsilane and 1,4-cyclohexadiene as hydrogen donors. This procedure tolerated various alkenyl compounds with fluoro, chloro, bromo, and iodo substituents, and the desired alkyl halides were isolated in moderate to good yields (Scheme 44).…”
Section: Osmium-based Catalystsmentioning
confidence: 99%
“…Post 2014, this MH HAT hypothesis was suddenly and widely adapted in research articles and literature reviews to characterize the field. 5,6,7,24,27,397 …”
Section: Mechanistic Overviewmentioning
confidence: 99%